Satisfacción del cliente en la Lavanderia "La Espuma" de la ciudad de Babahoyo, periodo 2022. - Rodríguez Márquez, Miguel Enrique (2023)
La Espuma laundry is a service microenterprise and is specifically dedicated to offering garment washing services, within the market of the city of Babahoyo. It is a company that has more than a decade of experience in the market and has been located in various strategic locations in the city, which has led to the fact that 74% of customers are practically new customers who have an interaction with the laundry, one year or less. The main purpose of the investigation was to know the perception of the users of the company, regarding the satisfaction they have in relation to the service provided. A descriptive methodology was used with a quantitative and qualitative approach. In the study, the line of research was considered: Administrative Financial Management, tax, audit and control, in the same way the research subline: Marketing and commercialization, established within the Business Career of the School of Administration. Among the main results, it was possible to determine that there is a positive perception of the users, who stated that they were satisfied with the customer service and in general with the laundry service offered. It was possible to establish that almost half of the users of the laundry "La Espuma" have problems with the availability of time to access the laundry service, for which the company established a strategic response of home service, to facilitate access service. There is great loyalty from its users, the same ones who are willing to recommend the service to other people.